Typifications, new combinations and new synonyms in Indian Impatiens (Balsaminaceae) - Singh, Rajeev Kumar; Borah, Dipankar; Taram, Momang (Biodiversity: Research and Conservation, 2021)
One neotype, three second-step lectotypes and fourty lectotypes are designated for fourty four names in Indian Impatiens to fix the identity and to avoid the misapplication of names. Thirty nine names are synonymized, after a detailed ecological study of live plants in the field and examination of herbarium specimens including types. Six new combinations with change in their status are proposed for six taxa.